2012
DOI: 10.1108/17570971211225127
|View full text |Cite
|
Sign up to set email alerts
|

Integrating addiction and mental health networks to improve access to treatment for people with alcohol and drug‐related problems: a qualitative study

Abstract: PurposeImprovement in Access to Treatment for People with Alcohol and Drug Related Problems (IATPAD) was a European study that detected barriers and facilitators to accessing treatment for patients with alcohol and drug‐related problems. This article seeks to compare the findings from a qualitative study with patients and staff in Catalunya (Spain).Design/methodology/approachThe paper describes a multi‐centre, qualitative study. A purposive sample of 47 staff, from a randomly selected sample of the three main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In addition, patients may have been more likely to not complete the AUDIT-C if they did not want to make their clinicians aware of their alcohol problems and if this were to happen they would have been excluded from the present audit, or they may have disproportionately under-reported their levels of alcohol use relative to others who completed the audit. The three hypotheses above may be supported by the literature on access to mental health services whereby several studies have reported that patients with alcohol or other substance abuse disorders comorbid to common mental disorders are more likely to be turned down for treatment in specialist addiction and specialist mental health services, and patients with these comorbidities are more likely to have experienced negative staff attitudes towards them, influencing their decisions to access treatment (Fonseca et al, 2012; Tocque et al, 2011). The appropriateness of treating common mental disorders comorbid for AUD in IAPT may depend not on the severity of the alcohol misuse (if we accept that those with established dependence are unlikely to be referred to IAPT), but on the confidence and competence of the staff to work with such problems and on the timeline and relationship between the common mental disorder and the alcohol misuse.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, patients may have been more likely to not complete the AUDIT-C if they did not want to make their clinicians aware of their alcohol problems and if this were to happen they would have been excluded from the present audit, or they may have disproportionately under-reported their levels of alcohol use relative to others who completed the audit. The three hypotheses above may be supported by the literature on access to mental health services whereby several studies have reported that patients with alcohol or other substance abuse disorders comorbid to common mental disorders are more likely to be turned down for treatment in specialist addiction and specialist mental health services, and patients with these comorbidities are more likely to have experienced negative staff attitudes towards them, influencing their decisions to access treatment (Fonseca et al, 2012; Tocque et al, 2011). The appropriateness of treating common mental disorders comorbid for AUD in IAPT may depend not on the severity of the alcohol misuse (if we accept that those with established dependence are unlikely to be referred to IAPT), but on the confidence and competence of the staff to work with such problems and on the timeline and relationship between the common mental disorder and the alcohol misuse.…”
Section: Discussionmentioning
confidence: 95%
“…For those who do access treatment, these issues can give rise to significant treatment delays and to poorer outcomes (e.g. Fonseca et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As your drug use increases, you may ind that it's increasingly dif icult to go without the drug. Attempts to stop drug use may cause intense cravings and make you feel physically ill (withdrawal symptoms) [3].…”
Section: Causes Of Drug Abusementioning
confidence: 99%
“…There is a growing body of evidence to suggest that participants in drug and alcohol treatment programmes, in addition to stopping use of their substance/s of choice, report feeling better about their lives in broader terms (Fonseca et al . ; Minkoff ). However, while improvements in both drug use and psychological well‐being have been noted during treatment, the relationship between these two variables has not been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%